Hi
For the following equations
$\displaystyle Y=x+x^2-x^4 $
do the following steps are correct ?
$\displaystyle x+(x-x^2)(x+x^2)$
$\displaystyle x+x(1-x)(1+x)$
$\displaystyle x[1+1-x^2] $
$\displaystyle x[2-x^2]$
Thank you
No. The common factor is just $\displaystyle x$.
$\displaystyle Y=x+x^2-x^4$
$\displaystyle Y = x(1 + x - x^3)$
--------------
When you are unsure about a result, just try with some numbers. With your result, what you are saying is that :
$\displaystyle x + x^2 - x^4 = x(2 - x^2)$
Take $\displaystyle x = 2$. Thus we get :
$\displaystyle 2 + 2^2 - 2^4 = 2(2 - 2^2)$
And therefore your results suggests that $\displaystyle -10 = -4$
But $\displaystyle -10 \neq -4$, thus your result is wrong.